Eksplorasi Etnomatematika Pada Benteng Belgica Di Neira Maluku Tengah - Agustri Amelia Fajarwati; Alifiya Nur Faidah; Elma Joelian; Hafidzah Diina Hakiki; Riawan Yudi Purwoko (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
Ethnomathematics is the study of mathematics learning. One of the cultural assets in Indonesia is Belgica Fort which is located on Neira Island, Central Maluku, which has a pentagon shape on the outside. The purpose of this research is to know the history of Belgica Fort and to know the construction of Belgica Fort building which is associated with mathematics in geometric shapes. The research methodÂ is a document analysis by analyzing and reducing data from several articles that become references, with the conclusion that the Belgica Fort building is composed of various forms of flat and spatial shapes. The results of his research that learning mathematics on geometry material associated with Belgica Fort can be used as teaching materials and encourage students to be active in exploring their knowledge through observations made in this ethnomathematics-based learning.Â Keywords: Fort Belgica, Ethnomathematics, Geometry